MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP UNTUK MENGETAHUI PENGARUH PENDEKATAN KONTEKSTUAL - Siti Jenab; Mita Islamiyati; Ratna Sariningsih (IKIP Siliwangi, 2018)
This study aims to determine the improvement of mathematical communication skills of junior high school students from the influence of contextual approach. This research takes the form of a posttest pretest design that compares the influence of a contextual approach with a conventional approach. This study has a population that is all students of SMP class VII in Cianjur District while the sample is a student of class VII SMP Plus Al-Ittihad Cianjur. The samples were taken at random into experimental groups and control groups. Based on the data in the field, it can be concluded that the effect of improving mathematical communication ability of junior high school students who gain learning using contextual approach is better than conventional learning. Therefore, the effect of improving learning with contextual approach is much better while conventional learning is still very less.